Cognitive factors related to regular physical activity in college students - Teamur Aghamolaei; SedighehSadat Tavafian; Laleh Hasani (Tehran University of Medical Sciences, 2015)
Background & Aim: Despite the well evidenced health benefits of regular physical activity, many Iranian college students do not engage in physical activity sufficiently. The aim of this study was to assess cognitive factors related to regular physical activity in college students in Hormozgan University of Medical Sciences, Bandar Abbass, Iran. Methods & Materials: A total of 314 students from three schools of the Hormozgan University of Medical Sciences were selected randomly. Of the total number of students, 249 students filled out the questionnaires completely (response rate = 79.3%). Exercise Benefits/Barriers scale, Selfefficacy scale, Exercise norms scale, and Planning for exercise scale were used to assess cognitive factors regarding physical activity; the Cronbach's alpha of these scales were 0.87, 0.83, 0.73, and 0.82, respectively. Results: The mean age of participants was 21.7 ± 2.7. Of all the participants, 46.2% were male. Only 26.5% (n = 66) were engaged in regular physical activity. Perceived barriers to exercise, selfefficacy to exercise, planning for exercise, and exercise norms had a significant relationship with physical activity (P < 0.05). However, there was no significant relationship between perceived benefits to exercise and physical activity. Conclusion: For increasing physical activity in college students, self-efficacy and social support improvement is suggested.